The Role of Mindfulness-Based Programs in Improving the Quality of Marital Relationships: A Systematic Review - Afghani, Amani Abdel Aziz Abdul Ghaffar (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to define mindfulness, clarifying its characteristics, uses, and benefits. It also highlights the importance of mindfulness-based programs and their impact on enhancing the quality of marital relationships by pinpointing the most significant insights from earlier research in the field. Methods: To achieve the study’s objectives and to facilitate an in-depth exploration of prior research on the topic, the study employs the systematic review methodology, which helps in identifying the nature of mindfulness and illustrating the effectiveness of mindfulness programs in improving the quality of marital relationships. The study involves several sequential stages: articulating the study’s objectives clearly, establishing acceptance and exclusion criteria, designing a search strategy to find relevant studies, evaluating each study against predefined criteria using a form aligned with the research protocol, and finally analyzing the findings. Results: The study reveals that mindfulness-oriented programs designed for couples have the potential to improve overall well-being, quality of life, self-compassion, and mindfulness. Moreover, it shows a consistent trend across previous research indicating that mindfulness-based interventions among couples hold promise for enhancing the quality of their relationships, with two studies reporting a decrease in depression symptoms. Conclusions: The study demonstrates the importance of mindfulness for improving the quality of marital relationships and recommends integrating mindfulness practices into marriage and family therapy programs. Additionally, it suggests that people in charge and professionals in the field should receive training on mindfulness techniques through specialized workshops and courses.